Analysis of Parental Involvement in Providing Support to Karate Athletes - Rohmah, Tsania Nur; Candra, Adiska Rani Ditya; Pratama, Rivan Saghita; Ramadhan, Indra (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aimed to identify the level of parental involvement in supporting karate athletes’ performance, specifically through directive behaviour, praise and understanding, and active involvement. Materials and methods. The research method was descriptive quantitative. Data analysis technique using percentage. The research instrument used the Parental Involvement In Sport (PISQ) questionnaire. Participants totalled 30 athletes who were given questionnaires. Result. The results showed that the directive behaviour factor was 36.6%, praise and understanding 40%, and active involvement 30%. Overall the results of this study found that parental involvement in supporting the achievements of karate athletes was in the good, sufficient and lacking categories, namely 30%. Although there is involvement that falls into the good category, 36.6% of active parental involvement is classified as less. This indicates that some parents are too involved in their children’s physical activities, which can put excessive pressure and interfere with the interaction between athletes and coaches. Conclusions. The conclusion based on these results is that parental involvement has a positive influence on athlete achievement, this falls into the category of intrinsic motivation. Parents need to understand the limits of optimal involvement, focusing on emotional support and trust in the coach in coaching athletes. Coaches can collaborate with parents to provide an understanding of their respective roles in supporting athlete development. Further research is needed involving more samples and more complex analysis methods to explore the dynamics of parental involvement and its impact on overall athlete performance.